BAHASA JURNALISTIK PADA BERITA POLITIK PERTEMUAN JOKOWI-PRABOWO DI SITUS TEMPO.CO (EDISI PERTEMUAN JOKOWI-PRABOWO DI STASIUN MRT LEBAK BULUS) - Nurhidayanti Nurhidayanti; Alamsyah Alamsyah; Andi Fauziah Astrid (Ilmu Komunikasi UIN Alauddin Makassar, 2019)
This research is an adaptation of the results of the thesis research that was done jointly between students and lecturers. The study underwent minor modifications to the needs of journal articles. The research objective was to determine the appropriateness of the journalistic language used by Tempo.co by taking a political news template, the Jokowi and Prabowo Meeting at the Lebak Bulus MRT Station. This type of research is descriptive qualitative with the analysis of news texts using the theory of Haris Sumadiria. The results of this study found that the news presented by Tempo.co did not fully fulfill the characteristics of a good and correct journalistic language according to the Haris Sumadiria Theory. This is adjusted to the requirements of journalistic language, namely simple, concise, concise, straightforward, clear, clear, attractive, democratic, populist, logical, grammatical, avoiding speech, avoiding foreign words and terms, choosing the right word (diction), prioritizing sentences active, and avoid technical words or terms.